Silicon-nanowire based attachment of silicon chips for mouse embryo labelling1. Issue 6 (21st March 2015) - Durán, S.; Novo, S.; Duch, M.; Gómez-Martínez, R.; Fernández-Regúlez, M.; San Paulo, A.; Nogués, C.; Esteve, J.; Ibañez, E.; Plaza, J. A.
<x xml:space="preserve">Abstract</x> We develop chip-on-a-cell barcodes featuring silicon nanowires as nanoscale attachment to label living mouse embryos.